2021
DOI: 10.1051/e3sconf/202123400090
|View full text |Cite
|
Sign up to set email alerts
|

Food Waste reuse as a feed for organic chicken: A case study

Abstract: Since the food system will inevitably produce food waste, it is recommended that it be captured and recycled for more efficient use rather than being disposed of as solid household waste. Therefore, it is advantageous to promote food waste as poultry feed. In order to study the feeding feasibility of a poultry Lab- Prepared Feed (LPF) based on kitchen food waste as well as their nutritional value, the tests were carried out near Taza city on an organic chicken farm, in Eastern Morocco. The results of consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…notably in cities such as Oujda, where waste production continues to increase annually [81,127]. This poses a challenge for countries such as Morocco in managing the waste generated by their growing population [128].…”
Section: The Energy Potential From Recoverable Solid Waste and Woody ...mentioning
confidence: 99%
“…notably in cities such as Oujda, where waste production continues to increase annually [81,127]. This poses a challenge for countries such as Morocco in managing the waste generated by their growing population [128].…”
Section: The Energy Potential From Recoverable Solid Waste and Woody ...mentioning
confidence: 99%
“…Therefore, fresh fruit and veggie waste could be used to feed sheep, and their efficient reuse could reduce the damage to the environment caused by putting such waste in landfills ( Sahoo et al, 2021 ). This study may help recover food waste as chicken feed ( Mechkirrou et al, 2021 ). Improvements in feed consumption, body weight, liver and abdominal fat, and blood triglyceride levels were observed in broiler chicks fed dried orange leftovers ( Abbasi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most agricultural industries produce large amounts of residue every year. The waste materials have great potential in biomass with valuable solutions to animal nutrition problems (Mechkirrou et al 2021). In Indonesia, waste agro-industrial products including bananas are found in abundance.…”
Section: Introductionmentioning
confidence: 99%